Analysis of reverse tracing algorithm for the detection of DOS attacks in MANET. (2017) - Hemalatha, P.; Ananthi, J. Vijitha; Kalaivani, R.
Nowadays, successful communication was provided by the wireless network with high data rate services. The major strategies in wireless network were security and trustworthiness. Due to the denial of the service attacks, most of the communication was disrupted. That was overcome by a new proposed algorithm called reverse tracing algorithm, which helps to find the attackers through reverse tracing messages. If the acknowledgment is received after every successful transmission, that was considered a secure communication. If it did not receive the acknowledgement properly, that will be considered as an unsuccessful transmission. By using this reverse tracing algorithm, we can identify the attacks. Simulation were performed using network simulator tool and then parameters such as throughput, delay, drop rate, goodput and packet delivery ratio was analysed. Compared to the previous approaches, the proposed reverse tracing algorithm achieves good performance.